Genome-wide identification and expression analysis of SMALL AUXIN UP RNA (SAUR) genes in rice (Oryza sativa) - Chenhao Jia; Yujiao Shi; Hao Wang; Yaofang Zhang; Feng Luo; Zhibin Li; Yubing Tian; Xiangrui Lu; Zhongyou Pei (Plant Signaling & Behavior)
SMALL AUXIN UP RNAs (SAURs), the largest family of early auxin response genes, plays crucial roles in multiple processes, including cell expansion, leaf growth and senescence, auxin transport, tropic growth and so on. Although the rice SAUR gene family was identified in 2006, it is necessary to identify the rice SAUR gene due to the imperfection of its analysis methods. In this study, a total of 60 OsSAURs (including two pseudogenes) distributed on 10 chromosomes were identified in rice (Oryza sativa). Bioinformatics tools were used to systematically analyze the physicochemical properties, subcellular localization, motif compositions, chromosomal location, gene duplication, evolutionary relationships, auxin-responsive cis-elements of the OsSAURs. In addition, the expression profiles obtained from microarray data analysis showed that OsSAUR genes had different expression patterns in different tissues and responded to auxin treatment, indicating functional differences among members of OsSAUR gene family. In a word, this study provides basic information for SAUR gene family of rice and lays a foundation for further study on the role of SAUR in rice growth and development.